Dog and Cat Contact as Risk Factor for Human Toxocariasis: Systematic Review and Meta-Analysis - Merigueti, Yslla Fernanda Fitz Balo; Giuffrida, Rogerio; Silva, Rodrigo Costa da; Kmetiuk, Louise Bach; Santos, Andrea Pires Dos; Biondo, Alexander Welker; Santarém, Vamilton Alvares (Frontiers in Public Health, 2022)
Toxocariasis, a neglected parasitic zoonosis with worldwide distribution, has been reportedly associated to different risk factors in several epidemiological and meta-analysis studies. However, dog and cat contact (environmental and animal exposure) as isolated associated risk factor for children and adults remains to be fully established. Accordingly, the present meta-analysis has aimed to directly assess dog and cat contact for toxocariasis seropositivity in under-18 and adult persons, using a survey strategy of PubMed/Medline, Embase, Scopus and Scielo Databases, from January 2009 to December 2021. A meta-analysis model of random effects was applied to estimate odds ratio (OR) with 95% Confidence Interval (CI). The statistical heterogeneity was evaluated by the Cochran Q-Test and I2 values. A total of 41 transversal studies (n = 20.515 individuals) from different geographic regions (classified by the World Health Organization) were included herein. In overall, 1,882/13,496 (13.95%; 95% IC = 13.4–14.5) youngers and 513/7.019 (7.3%; 95% CI = 6.7–7.9) adults in contact with dogs or cats were serologically reagent for anti-Toxocara antibodies. Association of dog and cat contact was observed only in youngers, with both dogs (OR = 1.53; p < 0.0001) and cats (OR = 1.64; p = 0.0001). In addition, association of dog and contact and serology was statistically significant in populations of Americas (OR = 1.37; 95% CI = 1.1–1.7), Middle East (OR = 2.9; 95% CI = 1.6–5.1) and West Pacific (OR = 1.6; 95% IC = 1.3–1.9). In conclusion, contact with dogs and cats, particularly by younger individuals and in regions such as Americas, Middle East, and West Pacific, should be always a public health concern for toxocariasis. Moreover, dogs and cats should be periodically dewormed, washed and hair cleaned prior to contact with youngers. Finally, robust statistical results herein may serve as basis for future strategies and preventive measures for safer dog and cat contact.